ayuda por favor con procedimiento
-5(x+2)+3(x-1)=-x-10


Respuesta :

[tex] - 5(x + 2) + 3(x - 1) = - x - 10 \\ - 5x - 10 + 3x - 3 = - x - 10 \\ - 5x + 3x - 10 - 3 = - x - 10 \\ - 2x - 13 = - x - 10 \\ - 13 + 10 = - x + 2x \\ - 3 = x[/tex]

Respuesta:

[tex]x = - 3[/tex]

Explicación paso a paso:

[tex] - 5(x + 2) + 3(x - 1) = - x - 10[/tex]

[tex] - 5x - 10 + 3x - 3 = - x - 10[/tex]

[tex] - 5x + 3x - 3 = - x[/tex]

[tex] - 2x - 3 = - x[/tex]

[tex] - 2x + x = 3[/tex]

[tex] - x = 3[/tex]

Espero te sirva